Efektivitas psikoedukasi melalui media google sites dalam peningkatan pengetahuan bullying pada remaja SMP - Desi Waluya; Sifa Fauziah; Obar Obar (Holistik Jurnal Kesehatan, 2026)
Background: Adolescence is a developmental stage marked by the process of self-identity discovery. During this stage, adolescents are vulnerable to various problems, one of which is bullying. Lack of knowledge about bullying is one factor that can contribute to this behavior. Therefore, efforts are needed to improve adolescents' knowledge, one of which is a psychoeducational approach through digital media. Purpose: To analyze the effectiveness of psychoeducation through google sites in increasing knowledge about bullying among junior high school adolescents. Method: This quantitative study used a quasi-experimental one-group pre-test and post-test design. The population in this study were all 80 students at Cikalongkulon 4 State Secondary School. The sample size was 25 participants selected using a purposive sampling technique. Data were collected using a bullying knowledge questionnaire and statistically analyzed using the Wilcoxon Signed Rank Test. Results: Before psychoeducation, participants' knowledge was still suboptimal. After psychoeducation, knowledge improved in the majority of participants (92%) and was categorized as good. The statistical test results showed a p-value of 0.000 < 0.05, indicating that psychoeducation through Google Sites was effective in increasing knowledge about bullying among junior high school adolescents. Conclusion: Psychoeducation through Google Sites was effective in increasing knowledge about bullying among junior high school adolescents. This medium can be used as an alternative in implementing psychoeducation programs in schools, particularly in preventing bullying among adolescents.   Keywords: Adolescents; Bullying; Knowledge; Google Sites; Psychoeducation.